Makna Simbolis pada Tradisi Nyolong Iwa dalam Ritual Entas-Entas sebagai Upaya Tolak Bala di Desa Tosari, Kecamatan Tosari, Kabupaten Pasuruan: Kajian Antropolinguistik - Paulina, Marta; Rafflesiani, Merlcy; Permata, Nadila; Nur, Shofiyatu; Savia, Syaharani; Salwa, Tsamara; Oktavian, oko (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2022)
Tengger is an area at the foot of Mount Bromo and has a lot of cultural diversity, one of which is the Entas-Entas DeathCeremony. In the Entas-Entas Ceremony, there are several other traditions in it, one of which is the Nyolong Iwa Tradition.The Tenggerese believe that life does not belong to us, but only a deposit from God. This study aims to describe terms andsymbols in the Nyolong Iwa Tradition as an effort to reject reinforcements in Tosari Village, Tosari District, PasuruanRegency. The method used in collecting data in this study is the method of listening to the tapping technique. The datacollected was analyzed using the listening method, which is a method whose implementation is carried out by listening to theform of lingual texts and symbols in the ritual. The basic technique used in analyzing the data is the tapping technique bytapping the use of symbols in the form of free-talk listening techniques, recording techniques, and note-taking techniques.